Managerial decision modeling with spreadsheets - Balakrishnan, Nagraj; Render, Barry; Stair, Ralph M. (Pearson Education, 2014)
For courses on decision modeling through the use of spreadsheets. The perfect balance between decision modeling and spreadsheet use. It's important that textbooks support decision modeling courses by combining student's ability to logically model and analyze diverse decision-making scenarios with software-based solution procedures.